2010
DOI: 10.1007/s10661-010-1314-x
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial distribution of metals in top soils of Islamabad City, Pakistan

Abstract: Present study was conducted in rapidly growing city Islamabad, and surface soils were collected from three major land cover types viz., built-up, drain side, and green areas. A total of seven physicochemical parameters and 11 metals were determined in surface soils. Factor analysis based on principal component analysis explained total variance of 68.0%, 64.5%, and 60.2% of three land cover types and showed high loadings for major elements (Mg and K) in built-up and green area and Fe in drain side. Top soil pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 70 publications
5
26
1
Order By: Relevance
“…Its contamination received serious attention in both developing and developed nations (Nicholson et al 2003;Zhang et al 2007). The comparative study (Table 7) showed that the Pb concentrations in this study were high compared with other reports except one by Ali and Malik (2011). Lead is mainly present in organic and inorganic compounds.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Its contamination received serious attention in both developing and developed nations (Nicholson et al 2003;Zhang et al 2007). The comparative study (Table 7) showed that the Pb concentrations in this study were high compared with other reports except one by Ali and Malik (2011). Lead is mainly present in organic and inorganic compounds.…”
Section: Discussioncontrasting
confidence: 48%
“…The Zn concentration in both reference and target areas were higher than that of the national and international studies except Ali and Malik (2011). The high level of Zn can cause stunted growth and chlorosis in plants.…”
Section: Discussionmentioning
confidence: 63%
“…The interelemental correlation between these elements in this study may possibly be ascribed to the control of the elemental association by factors such as soil genesis and properties as well as anthropogenic impact on the environment. Table 4 shows the evaluation of the soil contamination using the percentage enrichment factor adapted from Loska and Weichula [30], and Ali and Malik [31]. Generally, the obtained results showed that %EF of the studied heavy metals depicted contamination of the topsoil; however, Zn had the highest %EF probably because the minimum concentration of Zn from the soil samples of the local brass industrial area was about ten times the obtained mean value from the control soils.…”
Section: Correlation Analysismentioning
confidence: 99%
“…(White et al 1997a;Romic and Romic 2003;McGrath et al 2004). A large number of researchers from Pakistan have employed chemometric and geo-statistical approaches in evaluating national metal loads in soils (Tariq et al 2005;Tariq et al 2006;Jan et al 2010;Ali and Malik 2011;Malik et al 2010a;Ali et al 2014). Ali and Malik (2011) employed kriging method (geo-statistics) for the identification of metal-contaminated hotspot areas in Islamabad.…”
Section: Chemometric and Gis Approaches In Evaluating National Soil Mmentioning
confidence: 99%